Open rule legislative bargaining - Volker Britz; Hans Gersbach (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
We consider non-cooperative bargaining on the division of a surplus under simple majority rule. We use the "open rule" bargaining protocol as originally suggested by Baron and Ferejohn (1989): Proposals can be amended before they are voted on. It is widely known that there are significant gaps in our understanding of open rule bargaining. In order to address these gaps, we provide a fresh analysis of a particularly simple class of equilibria. Our results shed new light on the efficiency and fairness implications of using an open vs. closed rule in bargaining. In particular, our results on the open rule model suggest that equilibrium delays tend to be longer, and surplus allocations tend to be less egalitarian than originally predicted by Baron and Ferejohn. Understanding the efficiency and fairness properties of different bargaining protocols is crucial for institutional design.
Keywords: C72; C78; D72; 330; Bargaining; Legislatures; Open Rules; Baron and Ferejohn; Stationary Equilibrium